Analisis Struktur Kepemilikan dalam Tata Kelola BUMDes: Studi Kasus BUMDes Agraprana Sumberjaya Kabupaten Bekasi - Fauzhiah, Silvia Nur; Utaminingtyas, Tri Hesti; Hasanah, Nuramalia (LPPM Universitas Negeri Jakarta, 2024)
The purpose of this study is to find out the ownership structure in the governance of Agraprana Sumberjaya BUMDes, Bekasi Regency and analyze a good ownership structure for BUMDes. This study uses a descriptive qualitative approach. The results of the study show that Agraprana BUMDes still rely on ownership from the village government, some people only play the role of administrators in BUMDes, even though BUMDes can still run to this day. The involvement between the community, the village government and other parties in the governance of BUMDes indicates that the purpose of the establishment of BUMDes itself has been implemented. The results and findings in the study as well as the implications will be explained in detail in the article.